Asian expert recommendation on management of skin and mucosal effects of radiation, with or without the addition of cetuximab or chemotherapy, in treatment of head and neck squamous cell carcinoma. Issue 1 (December 2016) - Zhu, Guopei; Lin, Jin-Ching; Kim, Sung-Bae; Bernier, Jacques; Agarwal, Jai; Vermorken, Jan; Thinh, Dang; Cheng, Hoi-Ching; Yun, Hwan; Chitapanarux, Imjai; Lertsanguansinchai, Prasert; Reddy, Vijay; et al.
Abstract With increasing numbers of patients with unresectable locoregionally advanced (LA) head and neck squamous cell carcinoma (HNSCC) receiving cetuximab/radiotherapy (RT), several guidelines on the early detection and management of skin-related toxicities have been developed. Considering the existing management guidelines for these treatment-induced conditions, clinical applicability and standardization of grading methods has remained a cause of concern globally, particularly in Asian countries. In this study, we attempted to collate the literature and clinical experience across Asian countries to compile a practical and implementable set of recommendations for Asian oncologists to manage skin- and mucosa-related toxicities arising from different types of radiation, with or without the addition of cetuximab or chemotherapy. In December 2013, an international panel of experts in the field of head and neck cancer management assembled for an Asia–Pacific head and neck cancer expert panel meeting in China. The compilation of discussion outcomes of this meeting and literature data ultimately led to the development of a set of recommendations for physicians with regards to the approach and management of dermatological conditions arising from RT, chemotherapy/RT and cetuximab/RT, and similarly for the approach and management of mucositis resulting from RT, with or without the addition of chemotherapy or cetuximab. These recommendations helped to adapt guidelines published in the literature or text books into bedside practice, and may also serve as a starting point for developing individual institutional side-effect management protocols with adequate training and education.